Public relations for the public good how PR has shaped America's social movements - Capozzi, Louis; Spector, Shelley (Public relations collection, 2016)
1. The public relations campaign to free Rosa Lee Ingram -- 2. A public relations-driven evolution -- 3. Fostering a new black identity -- 4. Michael Sam makes great gains for the LGBT -- 5. The war on tobacco -- 6. The campaign for tobacco-free kids -- 7. When music is the message -- 8. Battling the tide of public opinion to build support for a Jewish state -- 9. Feminism from the Feminine Mystique to Lean In -- 10. The American civil rights movement -- 11. The Triangle Shirtwaist Factory fire and the rise of the labor safety movement -- 12. The fight against income inequality -- 13. Taking depression out of the closet -- 14. The temperance movement -- References -- About the authors -- Index